Human Capital Profiling in Education: Teachers’ Competence in Integrating AR Technology for Character Education Development - Gita Hindrawati; Inayah Inayah; Iwan Hermawan; Suharmanto Suharmanto (Research Synergy Foundation, 2025)
Teachers represent the core human capital within educational systems, serving as the pivotal agents in embedding character education into early childhood curricula framed by the principles of child-friendly schools. This study aims to identify teachers’ competence following storytelling-based character education training and to examine their readiness to utilize Augmented Reality (AR) technology embedded in innovative storybooks as a medium for character formation among Early Childhood Education (ECE) students. Using a quantitative descriptive approach and cluster analysis, data were collected from ECE teachers who had completed training on storytelling and AR-based pedagogical practices. The descriptive findings reveal diverse levels of pedagogical knowledge, digital literacy, and creative implementation, while cluster analysis delineates teacher profiles based on readiness and competence dimensions. Grounded in Intellectual Capital Theory, this study conceptualizes teachers as strategic assets whose cognitive and relational capital underpin the effectiveness of educational innovation. Drawing on Experiential Learning Theory, the integration of AR storybooks is interpreted as a reflective and active learning process that enhances teachers’ capability to design meaningful, technology-enhanced learning experiences. The study contributes to the literature on human capital development in education by offering managerial implications for differentiated professional learning strategies that foster innovation capability and sustain intellectual capital growth in ECE institutions.